SISTEM AUDIT ISO 9001 : 2000 INTERNAL DAN EKSTERNAL PENDEKATAN PADA PENINGKATAN KEPUASAN PELANGGAN (STUDI KASUS PADA PT. MARGA MAJU JAYA) - Munir Azhari (Sekolah Tinggi Manajemen IMMI Jakarta, 2021)
Munir Azhari, ISO 9001:2000 Internal and External Audit System Approach to Improve Customer Satisfaction.Quality is an image which is very hungered for each. Every flexible pavement in giving service to customer, goodnessin the case of product service and also service. Congeniality quality of in flexible pavement service industries contextcan be defined to through various approach, but in principle is reaching of according to among result of activity tobe delivered by customers to service company.ISO 9000 representing one of the management system quality of which is on this time become especial choice toflexible pavement service which wish to apply concept from management system quality of consistently and is systematic.The company that has the ISO must commit that is all kind from the lower level until top management have to runthe ISO system in right way. In this chase PT. Marga Maju Mandiri runs ISO system on the tract. The relationshipbetween ISO 9001 : 2000 implementing with customer satisfaction can be see as the result such as repeat order, thatis the customers have got the satisfaction. PT. Marga Maju Mandiri has been running the philosophy of the ISO 9001: 2000 ,they are; what you do you write, what you write you do, what you did you record and safety factor.The implementation of the quality management concept that has been carried out properly and effectively throughfull commitment from the company management in service orientation at PT. Marga Maju Mapan will produceasphalt services whose quality is closer to meeting the satisfaction desired by customers in accordance with workstandards and specifications.